Genetic determinants of silver nanoparticle resistance and the impact of gamma irradiation on nanoparticle stability - Amira M. Mahfouz; Walaa A. Eraqi; Hala Nour El Din El Hifnawi; Alaa El Din Shawky; Reham Samir; Mohamed A. Ramadan (BMC Microbiology)
Abstract Background One of the main issues facing public health with microbial infections is antibiotic resistance. Nanoparticles (NPs) are among the best alternatives to overcome this issue. Silver nanoparticle (AgNPs) preparations are widely applied to treat multidrug-resistant pathogens. Therefore, there is an urgent need for greater knowledge regarding the effects of improper and excessive use of these medications. The current study describes the consequences of long-term exposure to sub-lethal concentrations of AgNPs on the bacterial sensitivity to NPs and the reflection of this change on the bacterial genome. Results Chemical methods have been used to prepare AgNPs and gamma irradiation has been utilized to produce more stable AgNPs. Different techniques were used to characterize and identify the prepared AgNPs including UV-visible spectrophotometer, Fourier Transform Infrared (FT-IR), Dynamic light scattering (DLS), and zeta potential. Transmission electron microscope (TEM) and Scanning electron microscope (SEM) showed 50–100 nm spherical-shaped AgNPs. Eleven gram-negative and gram-positive bacterial isolates were collected from different wound infections. The minimum inhibitory concentrations (MICs) of AgNPs against the tested isolates were evaluated using the agar dilution method. This was followed by the induction of bacterial resistance to AgNPs using increasing concentrations of AgNPs. All isolates changed their susceptibility level to become resistant to high concentrations of AgNPs upon recultivation at increasing concentrations of AgNPs. Whole genome sequencing (WGS) was performed on selected susceptible isolates of gram-positive Staphylococcus lentus (St.L.1), gram-negative Klebsiella pneumonia (KP.1), and their resistant isolates St.L_R.Ag and KP_R.Ag to detect the genomic changes and mutations. Conclusions For the detection of single-nucleotide polymorphisms (SNPs) and the identification of all variants (SNPs, insertions, and deletions) in our isolates, the Variation Analysis Service tool available in the Bacterial and Viral Bioinformatics Resource Center (BV-BRC) was used. Compared to the susceptible isolates, the AgNPs-resistant isolates St.L_R.Ag and KP_R.Ag had unique mutations in specific efflux pump systems, stress response, outer membrane proteins, and permeases. These findings might help to explain how single-nucleotide variants contribute to AgNPs resistance. Consequently, strict regulations and rules regarding the use and disposal of nano waste worldwide, strict knowledge of microbe-nanoparticle interaction, and the regulated disposal of NPs are required to prevent pathogens from developing nanoparticle resistance.